New approaches to pharmacological treatment of osteoporosis - Åkesson Kristina (The World Health Organization, 2003)
Osteoporosis has been recognized as a major public health problem for less than two decades. The increasing incidence of fragility fractures, such as vertebral, hip, and wrist fractures, first became apparent from epidemiological studies in the early and mid-1980s, when effective treatment was virtually unavailable. Pharmacological therapies that effectively reduce the number of fractures by improving bone mass are now available widely in countries around the world. Most current agents inhibit bone loss by reducing bone resorption, but emerging therapies may increase bone mass by directly promoting bone formation - as is the case with parathyroid hormone. Current treatment alternatives include bisphosphonates, calcitonin, and selective estrogen receptor modulators, but sufficient calcium and vitamin D are a prerequisite. The availability of evidence-based data that show reductions in the incidence of fractures of 30-50% during treatment has been a major step forward in the pharmacological prevention of fractures. With all agents, fracture reduction is most pronounced for vertebral fracture in high-risk individuals; alendronate and risedronate also may protect against hip fracture in the elderly. New approaches to pharmacological treatment will include further development of existing drugs, especially with regard to tolerance and frequency of dosing. New avenues for targeting the condition will emerge as our knowledge of the regulatory mechanisms of bone remodelling increases, although issues of tissue specificity may be difficult to solve. In the long term, information gained through knowledge of bone genetics may be used to adapt pharmacological treatments more precisely to each individual.